Formulation, Optimization and Evaluation of Ticagrelor Loaded Self Microemulsifying Chewable Tablets - M, Veerendra K; Masareddy, Rajashree S; Patil, Archana S; Bolmal, Udaykumar (Indian Journal of Pharmaceutical Education and Research, 2022)
Ticagrelor is a new generation Adenosine diphosphate receptor inhibitor drug which is highly lipohilic having poor aqueous solubility used in the treatment of Acute Coronary Syndrome and prevention of Thrombotic events like Stroke and Heart Attack. An approach has been made to develop Chewable tablets of drug loaded on Self-microemulsifying drug delivery systems (SMEDDS), screen suitable adsorbent for solidification of formulated SMEDDS and to study the effect of superdisintegrants in chewable tablets. Methods: On basis of Pseudoternary diagrams constructed for selected oil, surfactant and cosurfactant, SMEDDS formulation was formulated using Capmul MCM EP oil with surfactant (Cremophor RH 40) and co-surfactant (PEG 400) which was solidified using selected adsorbent. Chewable tablets were compressed by direct compression method using superdisintegrants. Results: IR Studies and DSC studies revealed compatibility and stability of drug in formulation. Compression blend containing Solidified SMEDDS possessed good flow and compressibility. Chewable tablets compressed using Soy Polysaccharides as super disintegrant showed least wetting and disintegration time, drug release of 97.68% within 30 min. Short term stability studies revealed no significant change in physical and chemical properties. Conclusion: These results suggest that the Ticagrelor loaded self microemulsifying chewable tablets can be a promising oral drug delivery system to improve the solubility and dissolution profile of Ticagrelor.
Keywords: Ticagrelor; SMEDDS; Adsorbents; Chewable tablets; Acute coronary; syndrome